Investors’ Preference Towards Financial Investments -Some Survey Evidence - Dhivya, R.; Sekar, C. (Indian Journal of Finance, 2010)
Banking in India has witnessed remarkable changes and development since the onset of the processes of liberalization, globalization, and privatization during early nineties. Fixed income securities are one of the most innovative and dynamic instruments evolved in the financial system ever since the inception of money. Based on the concept of interest and time-value of money, fixed income securities personify the essence of innovation and transformation, which have fueled the explosive growth of the financial markets over the past few centuries. Fixed income securities offer one of the most attractive investment opportunities with regard to safety of investments, adequate liquidity, flexibility in structuring a portfolio, easier monitoring, long term reliability and decent returns. They are an essential component of any portfolio of financial and real assets, whether in form of pure interest bearing bonds, innovative and varied type of debt instruments or asset-backed mortgages and securitized instruments. An important feature of the securities market is the depth and breadth of public participation in the market. Millions of households and individual investors provide a pool of capital and a diversity of decision-making that creates liquidity in the market and makes it dynamic.